Effects of the Communities That Care Prevention System on Youth Reports of Protective Factors - Kim, B. K. Elizabeth (Prev Sci, 2015)
Many interventions seeking to reduce problem behaviors and promote healthy youth development target both risk and protective factors, yet few studies have examined the effect of preventive interventions on overall levels of protection community wide. In a community-randomized controlled trial, this study tested the effect of Communities That Care (CTC) on protective factors in 24 communities across 7 states. Data on protective factors were collected from a panel of 4,407 youths in CTC and control communities followed from Grade 5 through Grade 8. Hierarchical linear modeling compared mean levels of 15 protective factors derived from the social development model in CTC and control communities in Grade 8, adjusted for individual and community characteristics and baseline levels of protective factors in Grade 5. Global test statistics were calculated to examine effects on protection overall and by domain. Analyses across all protective factors found significantly higher levels of overall protection in CTC compared to control communities. Analyses by domain found significantly higher levels of protection in CTC than control communities in the community, school, and peer/individual domains, but not in the family domain. Significantly higher levels of opportunities for prosocial involvement in the community, recognition for prosocial involvement in school, interaction with prosocial peers, and social skills among CTC compared to control youth contributed to the overall and domain specific results. This is consistent with CTC’s theory of change, which posits that strengthening protective factors is a mechanism through which CTC prevents behavior problems.